Investigation on Blade Angles Effect on Micro-Gravitational Water Vortex System via Simulation and Experimental Analysis - Kee Seng, Wong; Shirley, Johnathan Tanjong (Pena Cendekia Publishing, 2025)
Micro gravitational water vortex power plants offer a promising solution for generating electricity from renewable energy sources with minimal hydraulic pressure requirements. Increased energy generation results from an increased vortex formation. Thus, the design of a micro gravitational water vortex system aims to achieve a powerful artificial air-core vortex. This study focused on investigating the effect of different blade angles in a Kaplan turbine within a micro gravitational water vortex system. Computational fluid dynamics (CFD) simulations conducted using Ansys software provided detailed insights into fluid flow dynamics, while experimental validation of the numerical results involved computational design and modelling, fabrication of the blades prototype on a 3D printer, and experimental data collection. Three blade angles at 140°, 150°, and 160°, were examined to determine its effects on power efficiency, approximate power input, and output. Simulation results indicate that a blade angle of 140° yields the highest power efficiency, reaching an impressive value of 95.40%. This efficiency outperforms the other blade profiles investigated. Experimental results showed reasonable consistency with the numerical predictions, with errors between numerical and experimental value ranging from 4.5% to 27.6%. Findings presented in this paper emphasised the importance of blade angle selection in optimizing the performance of micro gravitational water vortex power plants. Valuable insights for the design and operation of this eco-friendly technology aid the advancement of green energy generation systems.